Integrated agribusiness in the dairy industry of Ukraine: main characteristics and success factors - Gereles , Anna; Galych, Oleksandr (Applied Studies in Agribusiness and Commerce, 2013)
Ukraine belongs to the TOP 20 global producers of milk. Despite its position, the Ukrainian dairy industry is suffering from a permanent deficit of raw milk supplied for processing. on average, in 2007–2011 over half of the produced raw milk did not reach the processors. one of the reasons behind this lasting trend is that the structure of initial production of raw milk is dominated by households (having a share of 80%); the latter produce milk mostly for their own consumption and leftovers are sold at marketplaces where they can get more attractive prices. nevertheless, already today we observe results of largescale investments into the industrial production of milk made in the last few years. This article stresses an important place of the dairy industry in the agriculture of Ukraine, as it provides the population of vital food products, many of which are strategic in the export potential. Authors present essential characteristics of the concepts “agro-industrial integration” and “agroholding”, discloses their role and place in the agrarian sector of the economy, and justifies the necessity of the creation an integrated production in the Ukrainian dairy sub-complex. The study aims at identification and description of latest trends in Ukraine’s dairy market. Moreover, authors present a successful Ukrainian example of Milkiland N.V. as one of the TOP 5 players in the Commonwealth of Independent States (CIS) dairy market.